(untitled) (Global Journal of Sciences, 2024)
In the context of fractional calculus, the concept of convexity is primarily used to tackle various challenges in both theoretical and applied research. This review paper aims to present Hermite–Hadamard (H-H) inequalities related to different classes of convex functions via Riemann-Liouville fractional integral operators.